Asuhan Keperawatan Bersihan Jalan Nafas tidak Efektif pada Ny. R dengan CA Paru di Ruang Edelweis Atas RSUD Kardinah Kota Tegal - Naufal Ulil Albab; Ikit Netra W (Jurnal Sehat Mandiri, 2023)
Lung cancer is a disease that arises due to the abnormal growth of body tissue cells which turn into cancer cells and can be interpreted as malignancy that originates from outside the lungs or originates from the lungs themselves, where abnormalities can be caused by a collection of genetic changes in the epithelial cells of the respiratory tract, which can lead to uncontrolled cell proliferation. This study aims to determine nursing care for Ny. R with ineffective airway clearance in the Upper Edelweiss room at Kardinah Hospital, Tegal City. The design of this research is descriptive through a case study of the patient Mrs. R with Ineffective Airway Clearance. Researchers collect data through the stages of anamnesis, observation, physical examination and documentation studies. The results of this research indicate a development in Mrs. R before and after implementation was given in the form of health education about effective coughing with the results of the patient's subjective evaluation saying that the shortness of breath had reduced, he could produce secretions, he still coughed although not often, and the results of the objective evaluation of the rhonchi sounds began to disappear, SPO2: 99%), oxygen 3 lpm nasal cannula (disconnect). Conclusion of the nursing problem Mrs. R, with ineffective airway clearance, the problem is partially resolved and for the next action plan, continue the intervention (monitor breathing patterns, monitor additional breath sounds, observe the ability to expel secretions, position semi- Fowler, give oxygen, collaborate with mucolytics).